1995
DOI: 10.1002/art.1780381122
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin‐induced modulation of inflammation in experimental arthritis

Abstract: Objective. To study the antiinflammatory effect of different doses of intraarticular somatostatin in experimental arthritis in rabbits. Methods. Chronic arthritis was induced by a single injection of fibrin into the knee joint of rabbits previously sensitized to this antigen. The effects of sequential intraarticular injections of somatostatin into the rabbit knee, at doses of 500, 750, and 1,000 μg, were monitored by measuringknee joint circumferences and hematologic parameters. The measurements were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…SMS reduces in ammation in experimental arthritis and ileal obstruction. 86,87 Similar bene cial effects on intestinal and colonic in ammation emerge from clinical observations in Crohn's disease and goldinduced enteritis. 88,89 SMS is able to reduce SP mediated in ammation induced by intestinal infection with Trichinell a spir alis 90 and SP enhanced neutrophil chemotaxis.…”
Section: Immunomodulatory Effects Of Somatostatinmentioning
confidence: 82%
“…SMS reduces in ammation in experimental arthritis and ileal obstruction. 86,87 Similar bene cial effects on intestinal and colonic in ammation emerge from clinical observations in Crohn's disease and goldinduced enteritis. 88,89 SMS is able to reduce SP mediated in ammation induced by intestinal infection with Trichinell a spir alis 90 and SP enhanced neutrophil chemotaxis.…”
Section: Immunomodulatory Effects Of Somatostatinmentioning
confidence: 82%
“…SRIF decreases the extravasation of plasma and leukocytes and may reduce synovial swelling through this mechanism (Karalis et al, 1994). Reduction of joint swelling by intra-articular injection of SRIF is also observed in a rabbit model of chronic arthritis (Matucci-Cerinic et al, 1995). In addition, histological studies in this model have revealed reduction of lymphocyte infiltration in the synovium and reduced vasculitis in SRIF-treated animals.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effecmentioning
confidence: 87%
“…Local application of SRIF-14 into the inflamed knee joint in rabbits was shown to prevent joint swelling and edema (34)(35)(36). SRIF and its analogs also inhibit the production and release of proinflammatory mediators, such as TNF␣, IFN␥, and interleukin-6 in a number of inflammatory disorders (3,4,37,38).…”
Section: Discussionmentioning
confidence: 99%